Deuterated forms of H3+ and their importance in astrochemistry. (23rd September 2019) - Caselli, P.; Sipilä, O.; Harju, J.
Abstract : At the low temperatures (approx. 10 K) and high densities (approx. 100 000 H2 molecules per cm −3 ) of molecular cloud cores and protostellar envelopes, a large amount of molecular species (in particular those containing C and O) freeze-out onto dust grain surfaces. It is in these regions that the deuteration of H3 + becomes very efficient, with a sharp abundance increase of H2 D + and D2 H + . The multi-deuterated forms of H3 + participate in an active chemistry: (i) their collision with neutral species produces deuterated molecules such as the commonly observed N2 D +, DCO + and multi-deuterated NH3 ; (ii) their dissociative electronic recombination increases the D/H atomic ratio by several orders of magnitude above the D cosmic abundance, thus allowing deuteration of molecules (e.g. CH3 OH and H2 O) on the surface of dust grains. Deuterated molecules are the main diagnostic tools of dense and cold interstellar clouds, where the first steps toward star and protoplanetary disc formation take place. Recent observations of deuterated molecules are reviewed and discussed in view of astrochemical models inclusive of spin-state chemistry. We present a new comparison between models based on complete scrambling (to calculate branching ratio tables for reactions between chemical species that include protons and/or deuterons) and models based on non-scrambling (proton hop) methods, showing that the latter best agree with observations of NH3 deuterated isotopologues and their different nuclear spin symmetry states. This article is part of a discussion meeting issue 'Advances in hydrogen molecular ions: H3 +, H5 + and beyond'.